Insights Into the Aerodynamic Versus Radiometric Surface Temperature Debate in Thermal‐Based Evaporation Modeling. Issue 15 (8th August 2022) - Mallick, Kaniska; Baldocchi, Dennis; Jarvis, Andrew; Hu, Tian; Trebs, Ivonne; Sulis, Mauro; Bhattarai, Nishan; Bossung, Christian; Eid, Yomna; Cleverly, Jamie; Beringer, Jason; Woodgate, William; et al.
Abstract: Global evaporation monitoring from Earth observation thermal infrared satellite missions is historically challenged due to the unavailability of any direct measurements of aerodynamic temperature. State‐of‐the‐art one‐source evaporation models use remotely sensed radiometric surface temperature as a substitute for the aerodynamic temperature and apply empirical corrections to accommodate for their inequality. This introduces substantial uncertainty in operational drought mapping over complex landscapes. By employing a non‐parametric model, we show that evaporation can be directly retrieved from thermal satellite data without the need of any empirical correction. Independent evaluation of evaporation in a broad spectrum of biome and aridity yielded statistically significant results when compared with eddy covariance observations. While our simplified model provides a new perspective to advance spatio‐temporal evaporation mapping from any thermal remote sensing mission, the direct retrieval of aerodynamic temperature also generates the highly required insight on the critical role of biophysical interactions in global evaporation research. Plain Language Summary: Water lost by plants through evaporation is strongly linked with the temperature at an unknown height within the canopy. Because this in‐canopy temperature cannot be typically measured by a satellite, the majority of the global evaporation models substitute this with skin temperature, or the near‐surface temperature observed by the satellite sensors. Such methods do not fully capture the physical and biological processes governing the magnitude and variability of plant water use under severe water stress, leading to substantial errors in water cycle monitoring in the dry regions. Here, we show how a simple model that requires no anticipated parameter, provides not only reasonable estimates of evaporation in a variety of dry and wet conditions, but also a better insight into the role of plant water stress and greenness in the difference between the in‐canopy temperature and skin temperature. This model offers an alternative and novel perspective that can be used in images from current and future thermal satellite missions to advance global plant water use mapping for several water management applications and to investigate the highly complex land‐atmosphere interactions and feedback mechanisms. Key Points: Aerodynamic temperature and evaporation well estimated from physical principles and available energy‐water limits in different ecosystems Water stress and vegetation cover influences the difference between aerodynamic and radiometric temperatures through plant homeostasis Non‐parametric model offers a parameter‐sparse approach describing evaporation, canopy conductance and vapor pressure deficit relationship